Prevention of ethno-religious radicalism among youth in Volga federal district - Elena S. Lukashenko, Sergei V. Ustinkin, Evgeniya M. Rogozhina, (Opción, 2019)
This article considers the measures taken by the regional ministry and department of youth policy of VFD concerning realization of the plan to increase the level of tolerance and conflict-free interethnic and interreligious interaction within the framework of Russian youth policy via project and program-target methods. As a result, it is necessary to teach young people conflict-free interreligious (and thus interethnic) interaction. In conclusion, variegated interethnic and inter-confessional composition of the population in VFD puts important tasks before regional ministries and departments of youth policy.